Polymorphisms in the host CYP2C19 gene and antibiotic-resistance attributes of Helicobacter pylori isolates influence the outcome of triple therapy - Ram M, Ravishankar; Teh, Xinsheng; Rajakumar, Tamayanthi; Goh, Khean Lee; Leow, Alex Hwong Ruey; Poh, Bee Hoon; Mariappan, Vanitha; Shankar, Esaki M; Loke, Mun Fai; Vadivelu, Jamuna (Journal of antimicrobial chemotherapy, 2019)
Objectives: Eradication of Helicobacter pylori is influenced by susceptibility to antimicrobial agents, elevated bacterial load and degree of acid inhibition, which can be affected by genotypes of drug-metabolizing enzymes [cytochrome P450 (CYP) 2C19 polymorphism]. Theoretically, the choice and dose of proton pump inhibitor may also influence the suppression of H. pylori infection. The CYP2C19 genotype has recently been found to have an impact on peptic ulcer healing, H. pylori eradication and therapeutic efficacy of proton pump inhibitors. Methods: Here, we investigated the impact of the CYP2C19 genotype polymorphism and the success of triple therapy (fluoroquinolones/metronidazole/clarithromycin) on antibiotic-resistant strains in eradicating H. pylori in human subjects with non-ulcer dyspepsia (NUD), in human subjects with peptic ulcer disease (PUD) and in asymptomatic human subjects (positive and negative for H. pylori infection). Results: Based on the CYP2C19 genotypes, determined by Droplet Digital PCR (ddPCR) analysis, we found 11.2%, 62.5% and 26.3% corresponding to rapid metabolizers, intermediate metabolizers and poor metabolizers, respectively. However, we did not find any significant effect for homozygous ABCB1 or CYP2C19*2 and CYP2C19*3 alleles. We detected several participants heterozygous for both ABCB1 and CYP2C19*2, CYP2C19*3 and CYP2C19*17 loci. The participants heterozygous for both ABCB1 and CYP2C19*2 and *3 loci should be defined as intermediate and poor metabolizers according to the haplotype analysis in the NUD, PUD and asymptomatic subjects. Conclusions: Consequently, fluoroquinolones/metronidazole/clarithromycin-based triple therapies can be used to eradicate H. pylori infection, if one does not know the CYP2C19 genotype of the patient.
Keywords: dospělí; Helicobacter pylori; Female; Adult; výsledek terapie; mladý dospělý; ženské pohlaví; Adolescent; Proton Pump Inhibitors; lidé; inhibitory protonové pumpy; Drug Resistance, Microbial; Anti-Bacterial Agents; Treatment Outcome; Aged, 80 and over; cytochrom P450 CYP2C19; Cytochrome P-450 CYP2C19; Male; Aged; Young Adult; polymorfismus genetický; kombinovaná farmakoterapie; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Helicobacter Infections; antibakteriální látky; Polymorphism, Genetic; Middle Aged; mladiství; infekce vyvolané Helicobacter pylori; antibiotická rezistence; Drug Therapy, Combination; Humans